Economic evaluation of using mulch from multipurpose trees in maizebased production systems in southwestern Nigeria - Kormawa, P.M.; Kamara, A.Y.; Jutzi, S.C.; Sanginga, N. (1999)
Cutting and carrying of mulch from established tree plots is an alternative to in situ mulch in agroforestry systems. Through the cut-and-carry method, the undesirable e ects of tree-crop competition characterized by in situ mulching can be avoided. An economic evaluation of the cut-and-carry method of providing nutrients for maize production was carried out based on investigations in south-western Nigeria. The results showed that the use of mulch from multipurpose trees (MPTs) through the cut-and-carry method contributed to higher maize grain yields than those obtained with fertilizer or in the untreated controls. However, because of high labour requirements and scarcity of land in the study area, providing nutrients for crop production by this method is unpro®table both in the short and the long term. This may serve as a constraint for the adoption of this technology by farmers. Alternative options requiring less labour and land requirements should be investigated in the quest to replace shifting cultivation.